2018
DOI: 10.1371/journal.pone.0201339
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the knowledge, explanatory models of illness, and patterns of healthcare-seeking behaviour of Fang culture-bound syndromes in Equatorial Guinea

Abstract: In 1994, the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) included “culture-bound syndromes” in its classification of psychiatric disorders and associated them with disease processes that manifest in behavioural or thought disorders that develop within a given cultural context. This study examines the definitions, explanatory models, signs and symptoms, and healthcare-seeking behaviours common to Fang culture-bound syndromes (i.e., kong, eluma, witchcraft, mibili, mikug, and nsamadalu). The F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
4
0
1
Order By: Relevance
“…A final set of mechanisms relate to cultural or subcultural influences. For example, the Fang ethnic group in Equatorial Guinea describe mibili as possession by evil spirits that manifests as auditory and visual hallucinations 130 . Cultural influences are complex and multifaceted, involving myriad interfaces along geographical, ethnic, and religious lines.…”
Section: [H3] Personal and Sociocultural Mechanismsmentioning
confidence: 99%
“…A final set of mechanisms relate to cultural or subcultural influences. For example, the Fang ethnic group in Equatorial Guinea describe mibili as possession by evil spirits that manifests as auditory and visual hallucinations 130 . Cultural influences are complex and multifaceted, involving myriad interfaces along geographical, ethnic, and religious lines.…”
Section: [H3] Personal and Sociocultural Mechanismsmentioning
confidence: 99%
“…The Local Explanatory Models of Illness framework postulates that clinical knowledge needs to be combined with an understanding of local discourses and illness representations (53). Indigenous healing is an oft-neglected resource and valued tradition in African societies that has been marginalized by the hegemonic dominance of mainstream Euro-western medicine Explanatory frameworks that contributed to the model.…”
Section: Contribution Of Local Explanatory Models Of Illness To the M...mentioning
confidence: 99%
“…Several studies over the years have identified that social, historical, and cultural representations of mental health among people of African descent played an important role in how mental illness was experienced and treated (e.g., Gopalkrishnan, 2018; Irankunda et al, 2017; Jimenez Fernandez et al, 2018; Monteiro & Balogun, 2014). These socio-cultural representations of mental health influenced perceptions about the nature, cause, and course of mental illness (Sodi & Bojuwoye, 2011) and have been reported to be prevalent among several African communities.…”
Section: Mental Illness Representations In the African Diasporamentioning
confidence: 99%